Extensions and applications of the Bohm criterion. (April 2015) - Baalrud, Scott D; Scheiner, Brett; Yee, Benjamin; Hopkins, Matthew; Barnat, Edward
Abstract The generalized Bohm criterion is revisited in the context of incorporating kinetic effects of the electron and ion distribution functions into the theory. The underlying assumptions and results of two different approaches are compared: the conventional 'kinetic Bohm criterion' and a fluid-moment hierarchy approach. The former is based on the asymptotic limit of an infinitely thin sheath (λD/l = 0), whereas the latter is based on a perturbative expansion of a sheath that is thin compared to the plasma (λD/l ≪ 1). Here λD is the Debye length, which characterizes the sheath length scale, and l is a measure of the plasma or presheath length scale. The consequences of these assumptions are discussed in terms of how they restrict the class of distribution functions to which the resulting criteria can be applied. Two examples are considered to provide concrete comparisons between the two approaches. The first is a Tonks–Langmuir model including a warm ion source (Robertson 2009 Phys. Plasmas16103503). This highlights a substantial difference between the conventional kinetic theory, which predicts slow ions dominate at the sheath edge, and the fluid moment approach, which predicts slow ions have little influence. The second example considers planar electrostatic probes biased near the plasma potential using model equations and particle-in-cell simulations. This demonstrates a situation where electron kinetic effects alter the Bohm criterion, leading to a subsonic ion flow at the sheath edge.